Daycare Caregivers’ Role In Instilling Islamic Values In Early Childhood - Rizka Harfiani; Inggit Djuningsih (Al-Fikru: Jurnal Ilmiah, 2026)
This study examines the role of daycare caregivers in instilling Islamic values in early childhood at Rumah Bune Islamic Daycare, Bekasi. Previous studies have predominantly focused on formal teachers, while the contribution of caregivers who interact intensively with children through daily caregiving activities remains underexplored. This study employs a qualitative approach with a case study design, collecting data through participant observation, semi-structured interviews, and document analysis. The findings show that caregivers perform a strategic informal tarbiyah role through three mechanisms: habituating worship and thaharah within daily caregiving routines; providing direct role modeling through eating, sleeping, personal hygiene, and religious practices; and affectively reinforcing Islamic values through intensive attachment-based relationships. These findings demonstrate that caregivers are not merely childcare providers but also informal tarbiyah agents who complement the role of Islamic Religious Education teachers in developing children's Islamic character. The novelty of this study lies in conceptualizing caregivers as a “Tarbiyah Bridge” that connects formal academic learning spaces with children's everyday life experiences, a perspective that remains underexplored in the literature on Islamic early childhood education in Indonesia.